IN-SERVICE TEACHERS’ EXTENT OF TECHNOLOGY INTEGRATION IN TEACHING: AN INQUIRY - LIQUIGAN, MARK LESTER B. (International Journal of Arts, Sciences and Education, 2022)
Abstract The purpose of this study was to examine and conduct a pairwise correlation on technological pedagogical topic knowledge, in-service teachers’ exposure to technology, the level of technology integration into teaching, and their knowledge, abilities, and attitudes regarding technology usage in teaching. The correlational research design was the best fit for this research study since it allowed the researcher to assess the differences between variables. A total of 188 in-service teachers participated in the study. Female teachers were shown to be more creative than male teachers in establishing new and distinctive approaches for using ICT-assisted lecture presentations, as well as having a strong dedication to encouraging learners’ success. Furthermore, public school instructors have better levels of proficiency in the use of technology and instructional materials to support their teaching than their private school counterparts. This research also shows that the participants’ field of specialization and school type are both important factors of the amount of technology brought into the classroom.